Contemporary Issue of Destination Marketing: The Impact of Flood and Drought towards Water Supply in Kuala Lumpur - Zaki, Nur Amalina Mohamad; Padlee, Siti Falindah; Zulkiffli, Siti Nur ‘Atikah; Sulaiman, Nor Fatimah Che; Sulaiman, Mohd. Sofiyan; Ariffin, Effi Helmy; Ideris, Marini Mohamad (CENTRAL ASIA AND THE CAUCASUS, 2021)
As a result of globalisation, destination marketing has become essential as cities, states, regions and countries compete with one another to attract huge investment and tourists. In order for these destinations to compete effectively, it is essential to explore how natural hazard may have impacted the destination. Basic utilities such as water resources could have been impacted by natural hazards. To date, little is known on the impact of natural hazards towards water supply which may directly and indirectly affect the destination image. Information on the characteristics of natural hazards, namely flood and drought, (i.e, the time duration, location and the severity) based on the individual destination are also not known. Hence, the main objective of this study is to understand the economic and socio-economic aspects natural hazards (flood and drought) on water supply. To fulfill the research gap, a qualitative study was performed. Specifically, two (2) focus group discussions were executed to household representatives of the Federal Territory of Kuala Lumpur in regards to natural hazards; flood and drought. Based on the research findings, there is no issue of water supply associate with the flood crisis. However, there are mix opinions on the correlation of drought event and water supply, with majority believe that there is no correlation which occur between drought event and water supply of the Federal Territory of Kuala Lumpur. The findings of this qualitative study may serve as the foundation for a quantitative study (i.e., developing sets of questionnaires), and may contribute for policy makers and water providers in comprehending the issue and in taking the precaution measure prior to the occurrences of natural hazards.